Association polymorphism of guanine nucleotide–binding protein β3 subunit (GNB3) C825T and insertion/deletion of the angiotensin-converting enzyme (ACE) gene with peripartum cardiomyopathy - Dewi, Ivana Purnama; Wardhani, Louisa Fadjri Kusuma; Maghfirah, Irma; Dewi, Kristin Purnama; Subagjo, Agus; Alsagaff, Mochamad Yusuf; Nugroho, Johanes (Frontiers in Cardiovascular Medicine, 2023)
Introduction: Peripartum cardiomyopathy (PPCM) is a potentially life-threatening pregnancy-related heart disease. Genetic roles such as gene polymorphisms may relate to the etiology of PPCM. This study analyzes the association between single nucleotide gene polymorphism (SNP) guanine nucleotide-binding proteins beta-3 subunit (GNB3) C825T and insertion/deletion (I/D) of angiotensin converting enzyme (ACE) gene with the incidence of peripartum cardiomyopathy (PPCM). Methods: An analytic observational study with a case-control design was conducted at Integrated Cardiac Service Center of Dr. Soetomo General Hospital, Surabaya, Indonesia. The PPCM cases and controls were enrolled. Baseline characteristic data were collected and blood samples were analyzed for Single Nucleotide Polymorphism (SNP) in GNB3 C825T and I/D in the ACE by polymerase chain reaction (PCR), restriction fragment length polymorphism (RFLP), and Sanger sequencing. We also assess ACE levels between different ACE genotypes using a sandwich-ELISA test. Results: 100 patients were included in this study, 34 PPCM cases and 66 controls. There were significant differences in GNB3 TT and TC genotypes in the case group compared to the control group (TT: 35.3% vs 10.6%, p = 0.003; TC: 41.2% vs 62.5%, p = 0.022). TT genotype increased the risk of PPCM 4.6 fold. There was also a significant difference in the ACE DD genotype in the case group compared to the control group (26.5% vs 9.1%, p = 0.021). DD genotypes increased the risk of PPCM by 3.6 fold. ACE levels were significantly higher in the DD genotype group than in the ID and II genotypes (4356.88 ± 232.44 pg/ml vs 3980.91 ± 77.79 pg/ml vs. 3679.94 ± 325.77 pg/ml, p<0.001). Conclusion: TT genotype of the GNB3 as well as DD genotype of ACE are likely to increase the risk of PPCM. Therefore, these polymorphisms may predispose and a risk factor for PPCM incidence. ACE levels were significantly higher in the DD genotype group, which certainly had clinical implications for the management of PPCM patients in administration of ACE inhibitors as one of therapy option.